Identification of high potential bays for habs occurrence in Peninsular Malaysia using PALSAR remote sensing data - Pour, A. B. (International Society for Photogrammetry and Remote Sensing, 2016)
Increasing frequency, intensity, and geographic distribution of Harmful algal blooms (HABs) poses a serious threat to the coastal fish/shellfish aquaculture and fisheries in Malaysian bays. Rising in sea level, shoreline erosion, stresses on fisheries, population pressure, interference of land-use and lack of institutional capabilities for integrated management make major challenges. Recent investigations and satellite observations indicate HABs originated from specific coast that have favourable geographic, geomorphic and coastal geology conditions to bring the green macro algae from the coast offshore. Therefore, the identification of high HABs frequented bays using remote sensing and geology investigations in Malaysian waters is required to reduce future challenges in this unique case. This research implemented comprehensive geomorphic and coastal geology investigations combined with remote sensing digital image processing approach to identify Malaysian bays frequented with HABs occurrence in Malaysian waters territory. The landscape and geomorphological features of the Malaysian bays were constructed from the Phased Array type L-band Synthetic Aperture Radar (PALSAR) remote sensing satellite data combined with field observations and surveying. The samples for laboratory analysis were collected from the sediment stations with different distance across shorelines features and watersheds of the Johor Bahru estuary. This research identified that semi-enclosed bays such as Kuala Lumpur and Johor Bahru bays with connection to estuaries have high potential to be frequented with HABs occurrence.